The Influence of Physical Exercise on the Consumer Psychology and Behaviour of Different Economic Sports Audiences - Hao Lu, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
In order to promote healthy economic growth and develop China's sports industry. Based on a cross theoretical model and a cognitive decision-making model for sports consumption, the author proposes a study on the impact of physical exercise on the consumption psychology and behaviour of different economic sports audiences. A comparative analysis was conducted on the sports consumption psychology at different stages of exercise behaviour using survey data from 587 intellectuals. In the pre intention action stage, the demand for sports consumption shows an upward trend; in the persistence stage, sports consumption needs to decrease slightly; As the stage of exercise behaviour progresses, the satisfaction of sports consumption shows a gradually increasing trend; Improving satisfaction is beneficial for exercisers to transition to a higher-level behavioural stage. Sports marketing regards the first three stages of exercise behaviour as the stages of cultivating sports consumers, promote more sports consumers to develop into the exercise behaviour persistence stage faster through low-priced products and satisfactory services, and pursue long-term sustainable development benefits generated during the exercise persistence stage. In addition, through recognizing the influence of physical exercise on consumer behaviour, businesses and policymakers can devise targeted strategies to promote sports participation and sports-related consumption, fostering a healthier and more engaged society.